Enhancement of UV Excited Photoluminescence by Fabry-Perot Microcavity - Chunxian Tao; Jun Ruan; Dong Liang; Zhaoxia Han; Liang He; Ruijin Hong; Xiao Cui; Dawei Zhang (Journal of Spectroscopy)
A light-emitting microcavity with the structure of dielectric mirror/phosphor coating/dielectric mirror for the enhancement of PL efficiency excited under UV light was designed and fabricated. The fluorescence emission of Lumogen S0795 coating within microcavity structure is significantly enhanced compared with the coating on bare substrate. The measurement results indicate the possibility of developing front illuminated CCD based on optical resonant cavity for UV-visible imaging with higher sensitivity.